The barque George Henry, from Frobisher's Bay, had arrived at St. John's
A short account of the progress of Charles Francis Hall's 1860-3 Frobisher Bay expedition to determine the fate of lost explorer Sir John Franklin, given upon the arrival of the bark George Henry at St. John's. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.